Key elements in the successful clinical experience of pre-service teachers / Norshiha Saidin - Saidin, Norshiha (Universiti Teknologi MARA Cawangan Selangor, 2011)
This paper explores final year pre-service teachers’ perception of the key elements critical to successful in-school clinical experience. The paper focuses on how a teacher education program aids prospective teachers in their transition from students to professionals who are able to take responsibility for others. Data was collected through a survey given to 104 TESL student teachers who had undergone 14 weeks of guided clinical experience. A focus group interview provided further data to explore the learning moments from the perspective of these student teachers. The key elements identified by student teachers for successful school placement are effective communication, especially in building positive personal and professional relationships with mentor teachers and supervisors as well as verbalizing shared reflections. The data provide insight into how ideas about teaching, learning and mentoring evolve and about the role of mentors and student teachers. Another critical element concerned how to communicate and reach out to troubled and reluctant learners.